2012
DOI: 10.1021/jp3089403
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Binary Ionic Liquid–Aprotic Solvent Electrolyte Mixtures

Abstract: The properties of mixtures of ionic liquids (ILs) with a variety of different aprotic solvents have been examined in detail. The ILs selected bis(trifluoromethanesulfonyl)imide (TFSI − ) salts with N-methyl-N-pentylpyrrolidinium (PY 15 + ), -piperidinium (PI 15 + ), or -morpholinium (MO 15 + ) cationsenabled the investigation of how cation structure influences the mixture properties. This study includes the characterization of the thermal phase behavior of the mixtures and volatility of the solvents, density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 30 publications
5
63
0
Order By: Relevance
“…9 AN, γ-BL, and PC significantly differ in terms of their macrosopic polarity (relative permittivities at 298. 15 21 and 2.5120 mPa s, 17 respectively) and, hence, can greatly modify the physicochemical properties of ILs, as it was shown, for example, by Couadou et al 22 With dependence on the desired set of properties, an optimized composition can be found that can be further used in electric double-layer capacitors and other electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…9 AN, γ-BL, and PC significantly differ in terms of their macrosopic polarity (relative permittivities at 298. 15 21 and 2.5120 mPa s, 17 respectively) and, hence, can greatly modify the physicochemical properties of ILs, as it was shown, for example, by Couadou et al 22 With dependence on the desired set of properties, an optimized composition can be found that can be further used in electric double-layer capacitors and other electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…3.3a, the viscosity of PY 15 TFSI-PC mixtures is greater than the viscosity of PY 15 TFSI-DMC and PY 15 TFSI-AN mixtures [66]. Moreover, as would be anticipated, the increase in the viscosity of PY 15 TFSI-solvent mixtures was correlated to the increase in the viscosity of the pure solvents [65].…”
Section: Viscositymentioning
confidence: 93%
“…In the literature, it is commonplace to form eutectic mixtures by adding molecular solvents to ILs. For example, Fox, Borodin, and co-workers examined the effects of adding three molecular solvents-propylene carbonate (PC), dimethyl carbonate (DMC), and acetonitrile (AN)-to an IL, N-methyl-N-pentylpyrrolidinium bis(trifluoromethanesulfonyl) imide (PY 15 TFSI) via experimental measurements [65] and molecular dynamics simulation [66]. The Einstein relation was used to compute the viscosity of the experimentally and computationally characterized PY 15 TFSI-solvent mixtures [66].…”
Section: Viscositymentioning
confidence: 99%
“…Aqueous systems have also been studied 4d. 7 Fox et al pointed out that a variety of solvent properties may influence their suitability, including their donor numbers, flexibility, viscosity, permittivity, and the number of electron lone pairs 8. Likewise, an extensive analysis of the system [Pyrr 14 ][NTf 2 ] ([Pyrr 1 a ] + =N‐ n ‐alkyl‐ N ‐methylpyrrolidinium, where a describes the number of carbon atoms of the n ‐alkyl chains attached to the N atom, Tf=SO 2 CF 3 ) by Zarrougui et al showed a dependence of ion solvation on the IL concentration 9.…”
Section: Introductionmentioning
confidence: 99%
“…7b, 12, 13 In the course of these aggregation phenomena, the motion of the cations and anions is also likely to become more correlated 11. In contrast, the often more viscous polar solvents tend to break ion–ion interactions and create a solution in which a greater share of the ions is free or, more accurately, solvated only by solvent molecules 8. A variety of such mixtures comprising ILs and molecular solvents has been tested in both Li‐ion batteries and supercapacitors, with promising results, also with respect to safety considerations 4c.…”
Section: Introductionmentioning
confidence: 99%